ANALISIS KINERJA BANK UMUM SYARIAH DENGAN MENGGUNAKAN PENDEKATAN CAMEL DAN PENDEKATAN ISLAMICITY PERFORMANCE INDEX TAHUN 2013-2018 - Yolanda, Rista; Verdiyanti, Verdiyanti; Andjioe, Oscar Ryanandi (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2020)
The method used in this research is descriptive method using quantitative. The data source used is secondary data. Results: the performance of Islamic banks with the standard approach of financial ratios 2013-2018 showed